(untitled) (Social and Environmental Law Journal, 2024)
This research aims to reflect on the health of the population in contemporary Brazil, with a focus on the situation of Black women. To achieve this, we will analyze recent statistical data released by the Brazilian Institute of Geography and Statistics (IBGE) in the Demographic Census and various official documents from the Ministry of Health. Thus, we will discuss the guidelines of the National Policy for the Integral Health of the Black Population, highlighting prevalent diseases, the health situation of Black women, mental health, and additional data that help us understand access to health in the country and public policies concerning health in the current context. The study involves a preliminary statistical analysis with implications for guiding public health policies for local communities in northern Goiás, based on the Gender Violence Combat Observatory, a partnership between the State University of Goiás, North Campus Uruaçu, and the Federal Institute of Goiás, Uruaçu Campus.